National Determinants of Health: A Cross-National Aggregate Analysis - Schultz, David (Medicine, Law & Society, 2022)
Research indicates that many factors impact individual health. These factors include genetics, lifestyle choices, and access to health care or health care insurance. Some of these factors are beyond the control of individuals, such as genetics or congenital circumstances. In addition, some factors, although beyond individual control, are certainly malleable, such as public policy choices made by governmental bodies. This article undertakes a preliminary analysis to assess macro national variables that impact individual health. It amasses a cross-national aggregate database of key indicators of health and compares them to macro “environmental” variables to assess the impact they globally have on health. The goal here is to determine what impact, if any, factors not traditionally thought of as health-related impact the well-being of individuals. The conclusion is that the political structure of a state, along with several policies related to crime, pollution, and ethnic conflict can impact health. The implication of research is that many policies generally thought to be exogenous to health can actually impact it and therefore states need to think more broadly beyond simply access to health care or insurance in seeking to improve the health and well-being of its people.